PERKEMBANGAN TOR-TOR SOMBAH PADA PESTA RONDANG BITTANG DI SIMALUNGUN - RISTY YUNING TYAS (Universitas Negeri Medan, 2013)
Development Of Tor-Tor Sombah Rondang Bittang At A Party In Simalungun This research aims to find out how the procedures for the implementation and development of the rondang party bittang tor-tor sombah rondang bittang at a party. In this research, used the theory and understanding of related research topics, such as the theory of change and development of understanding. The time used to discuss about the development of tor-tor sombah rondang party bittang on in Simalungun was conducted for 3 months. The research is in district Sidamanik. As for the sample in this research is a part of the population, i.e. totalling 5. Data collection techniques include observation, interviews, the study of librarianship and documentation, and then in the analysis by qualitative descriptive method. Based on the research that has been done then it can be inferred that the Ordinance implementing the party rondang bittang when handled by Government begins with the activities of mamuhun and maranggir which later continued with the activities of the race, the race's traditional sports namely, marjalekkat, margalah and marlittun and the traditional art of the race, hagualon, taur-taur and urdou-urdou, sordam, tulila, sulim, vocal group, Simalungun, song Copyright race race fashion bridal Simalungun, Goddess, tor-tor usihan, huda-hudaToping-toping and tor-tor sombah. Development of tor-tor sombah can be seen in the prior period in 1953, after 1953, and during the 1980s. now a growing element is in motion the somb Keywords: Development, Tor-Tor Sombah